Prevalence of Anemia in Chronic Kidney Disease (Medicine Today, 2021)
Introduction: Anemia in CKD is associated with cognitive impairment, sleep disturbances, CKD progression, cardiovascular co morbidities, and higher mortality. Direct healthcare costs are higher in CKD patients with anemia.The aim of the present study was to evaluate the prevalence of anemia in chronic kidney disease patients at a tertiary level teaching hospital in Dhaka.Materials and Methods: It was an observational type of descriptive study, conducted in the Dhaka National Medical College, Dhaka, during the study period of January 2019 to April 2019. The study was approved by the institutional ethical committee.Results: Most of the patients (44.56%) belonged to the middle age group 40 - 60 years. Male patients (64.40%) are suffering from more CKD than the female patients (35.50%). Most of the patients (58.41%) are anemic. 45% CKD patients also suffering from diabetes mellitus. Most of the patients (51.48%) treated with oral iron agents for anemia in CKD patients.Conclusion: In this study most of the chronic kidney disease patients are anemic. Improving our understanding of the molecular mechanisms underlying anemia of CKD holds promise for developing pharmacological agents that more closely target the underlying pathogenic mechanisms of this disease for improved efficacy and reduced treatment related adverse outcomes.Medicine Today 2021 Vol.33(1): 54-57